The Drosophila auditory system. (16th October 2013) - Boekhoff‐Falk, Grace; Eberl, Daniel F.
<x xml:space="preserve">Abstract</x> Development of a functional auditory system in Drosophila requires specification and differentiation of the chordotonal sensilla of Johnston's organ (JO) in the antenna, correct axonal targeting to the antennal mechanosensory and motor center in the brain, and synaptic connections to neurons in the downstream circuit. Chordotonal development in JO is functionally complicated by structural, molecular, and functional diversity that is not yet fully understood, and construction of the auditory neural circuitry is only beginning to unfold. Here, we describe our current understanding of developmental and molecular mechanisms that generate the exquisite functions of the Drosophila auditory system, emphasizing recent progress and highlighting important new questions arising from research on this remarkable sensory system. WIREs Dev Biol 2014, 3:179–191. doi: 10.1002/wdev.128 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.